A hospitalidade na Romaria de Nossa Senhora de Caravaggio/ Farroupilha/ RS sob a ótica da Igreja Católica - Schvarstzhaupt, Rosalina Luiza Cassol (My University, 2018)
The issue of hospitality and welcoming people has aroused interest in the academic environment in this time marked by great human nobility resulting from factors taking place in different geographical spaces. In the religious dimension, pilgrimages have increased to sacred sites around the world. In the face of this, this study aims to assess the hospitality that is offered, by the Catholic Church, to the pilgrims coming to the Shrine of our Lady of Caravaggio, Farroupilha, RS, in the pilgrimage held annually on May 26. This paper is, therefore, focused on the hospitality that the Catholic Church offers to pilgrims from the analysis of the interviews conducted with the people that are part of the Church and who have been involved with the pilgrimage in different times. The discourse of these representations will be treated by the method of discursive textual analysis so as to understand how these people perceive the hospitality offered by the Church in this pilgrimage and how it takes place, with a view to contributing to Religious Tourism.
O tema da hospitalidade e acolhimento tem atraído interesse no meio acadêmico, neste tempo marcado por grande mobilidade humana, decorrente de fatores nos diversos espaços geográficos. Na dimensão religiosa, as peregrinações têm demonstrado crescente fluxo aos lugares sagrados, em todo o mundo. Diante disso, este estudo tem como objetivo analisar a hospitalidade que é oferecida pela Igreja católica aos peregrinos que chegam ao Santuário de Nossa Senhora de Caravaggio, Farroupilha, RS, na romaria que acontece anualmente em torno do dia 26 de maio. A pesquisa tem como objeto o estudo da hospitalidade que a Igreja católica oferece aos peregrinos, a partir da análise das entrevistas realizadas com sujeitos que fazem parte da Igreja e que tiveram envolvimento com a romaria em diversas épocas. O discurso dessas representações será tratado pelo método de análise textual discursiva, com vistas a conhecer a percepção que esses sujeitos têm sobre a hospitalidade da Igreja nessa romaria e como ocorre o acolhimento dos peregrinos, com vistas a contribuir para o Turismo Religioso
Keywords: Hospitalidade; Peregrinos e peregrinações; Caravaggio, Nossa Senhora de; Turismo - Aspectos religiosos; Devoção; Hospitality; Pilgrims and pilgrimages; Caravaggio, Our Lady of; Tourism Religious aspects; Devotion